2013
DOI: 10.1186/1471-2458-13-975
|View full text |Cite
|
Sign up to set email alerts
|

Association between health examination items and body mass index among school children in Hualien, Taiwan

Abstract: BackgroundTo assess the prevalence of obesity and major physical examination items including dental caries, myopia, pinworm, hematuria, and proteinuria among school children in Hualien, Taiwan. In addition, the health status differences between gender, grader, levels of residence urbanization, and body mass index (BMI) were examined.MethodsCross-sectional studies with a total of 11,080 students (age, 7–14 years) in grades 1, 4, and 7 were evaluated for weight, height, routine physical examination, and urine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 12 publications
7
16
0
1
Order By: Relevance
“…Recently, researchers have paid more attention to the potential influence of urbanisation on myopia, and the possible adverse effects of higher urbanisation levels have been verified . Family income may be a factor that reflects urbanisation levels to some extent, and the influences on myopia are complicated by the effects of housing type, lighting levels, parental education levels, and parental myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have paid more attention to the potential influence of urbanisation on myopia, and the possible adverse effects of higher urbanisation levels have been verified . Family income may be a factor that reflects urbanisation levels to some extent, and the influences on myopia are complicated by the effects of housing type, lighting levels, parental education levels, and parental myopia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] On application of binomial regression analysis, females were found to be 1.84 times risk of developing caries than males. The results were in concordance with study done by Chu et al ., (2013)[ 24 ] who found the females were 1.34 times risk of developing caries than males. This is perhaps due to the fact that girls are having the habit of taking snacks between meals because of their longer indoor stay in comparison to boys who mostly spend time in outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
“…1 Since 2007, all school children in Hualien have received a health examination including a urinalysis in grades 1, 4, and 7 by the same tertiary care hospital in eastern Taiwan. Our previous study reported that the overall prevalence of hematuria and proteinuria in 2010 among Hualien school children was 3.8% and 2.4%, respectively, 6 and increased prevalence of hematuria and proteinuria was found in the following years (unpublished data). Children with persistent isolated microhematuria have an increased risk for renal damage and CKD progression due to cytotoxic, oxidant, and inflammatory effects induced by heme or hemoglobin released from red blood cells.…”
Section: Introductionmentioning
confidence: 87%